Platelet and Erythrocyte Parameters in Type 2 Diabetic Moroccan Patients: A Cross-Sectional Study - Mhirig, Ibtissam; Harrar, Sara; Habibi, Leila; Sayagh, Sanae; Aboulmakarim, Siham (Journal of Laboratory Physicians, 2023)
Introduction Complete blood count parameters have gained renewed interest as predictors of endothelial dysfunction in type 2 diabetes mellitus (T2DM). Thus, the aim of this study was to observe the changes in platelet and erythrocyte parameters between diabetics and nondiabetics and to evaluate these changes in relation to glycemic control.Materials and Methods This cross-sectional study was performed in Mohammed VI University Hospital, Marrakech, Morocco, from January 2020 to July 2021. A total of 307 Moroccan patients were enrolled in this study, which included 222 diabetic patients and 85 nondiabetics. The diabetic patients were divided into two groups A (hemoglobin A1c [HbA1c] ≥ 6.5%) and B (HbA1c < 6.5%) according to their glycated hemoglobin levels (HbA1c). Biological parameters were processed as per the standard technique. Data analysis was performed using SPSS statistical software.Results A significant difference was mentioned regarding mean corpuscular volume (MCV) (p < 0.001), red blood cell distribution width (RDW) (p < 0.001), and volume/platelet count (p = 0.023) between diabetics and nondiabetics. MCV and RDW were lower in group B than group A (p = 0.004; p = 0.04), while MPV was higher (p = 0.342). RDW significantly and negatively correlated with HbA1c in diabetic population (r = –0.182; p = 0.006). On the other hand, a significant and positive correlation between MPV and HbA1c was mentioned (r = +0.184; p = 0.006).Conclusion Our study showed that RDW and MPV correlate with HbA1c in T2DM and can be used as a reproducible and inexpensive means to ensure proper control of glycemic status. Further studies are warranted to define specific RDW and MPV values predictive of complication risk in the diabetic population.
Keywords: glycated hemoglobin; mean platelet volume; red cell distribution width; type 2 diabetes mellitus